2010
DOI: 10.1017/s1049023x00008116
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Blood Transfusion Requirements in Preparation for a Major Earthquake: The Tehran, Iran Study

Abstract: Introduction:Tehran, Iran, with a population of approximately seven million people, is at a very high risk for a devastating earthquake. This study aims to estimate the number of units of blood required at the time of such an earthquake.Methods:To assume the damage of an earthquake in Tehran, the researchers applied the Centre for Earthquake and Environmental Studies of Tehran/Japan International Cooperation Agency (CEST/JICA) fault-activation scenarios, and accordingly estimated the injury-to-death ratio (IDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…20 Respondents identified HIV 1/2 virus, ABO typing, and Hepatitis B and C viruses as priority targets for a rapid POC device that can address the need for emergent blood donation screening during mass casualty events when traditional transfusion services infrastructure is destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…20 Respondents identified HIV 1/2 virus, ABO typing, and Hepatitis B and C viruses as priority targets for a rapid POC device that can address the need for emergent blood donation screening during mass casualty events when traditional transfusion services infrastructure is destroyed.…”
Section: Discussionmentioning
confidence: 99%
“…Regional blood need estimates were drawn from the published work of groups that have reviewed the injuries that result from major earthquakes and calculated the amount of blood that would be required to support all the surgeries required in the first 24 hours . Such published estimates based on Force 9 earthquake scenarios for Tehran, Iran, and Lima, Peru, cities with approximate populations of 10 million people each, led to similar estimates of 9000 units of RBCs needed to treat the casualties presenting in the first 24 hours . This suggests that Western Washington with half that population might want 4500 units of RBCs in the first 24 hours, 200 units of RBCs/hr.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Such published estimates based on Force 9 earthquake scenarios for Tehran, Iran, and Lima, Peru, cities with approximate populations of 10 million people each, led to similar estimates of 9000 units of RBCs needed to treat the casualties presenting in the first 24 hours. [9][10][11] This suggests that Western Washington with half that population might want 4500 units of RBCs in the first 24 hours, 200 units of RBCs/hr. Failure times were calculated as inventory divided by issue rate or the length of time the institution could sustainably issue blood before their inventory ran out if they issued at the maximum rate as determined above.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Tabatabaie et al. () highlighted that demand is highest during the first 24 hours of a disaster. Other concerns relate to the restriction on storage and transportation of blood products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Tabatabaie et al. () and Guo et al. () concluded that postearthquake first‐time donors are less likely to donate again in the absence of continuing motivation strategies.…”
Section: Literature Reviewmentioning
confidence: 99%